Effect of different types of organic manure on biomass yield, morphological characteristics and nutritive value of BLRI Napier-4 in Baghabari milk shed area, Sirajgonj (Asian Journal of Medical and Biological Research, 2016)
The trial was conducted at Bangladesh Livestock Research Institute (BLRI) regional station, Baghabari, Shajadpur, Sirajgonj to determine the biomass yield, morphological characteristics and nutritive value with the effect of different sources of organic manure such as biogas slurry, broiler litter and layer litter for fodder production. Significant (P fertilizer (26.56)> broiler litter (22.34)>layer litter (22.20). This study also showed that DM yield and survival percentage were also significantly (P?0.05) differed among the treatments. The DM% in all groups was mostly similar but DM yield (t/ha) was the highest (3.94) in biogas slurry and the lowest (3.13) in layer litter. The cost (Tk/ha) was significant (P0.01) effect of different organic manures on nutritive value of BLRI Napier-4. It may be suggested that biogas slurry may be used as sources of fertilizer for fodder cultivation.Asian J. Med. Biol. Res. December 2015, 1(3): 690-692